2016
DOI: 10.1080/02713683.2016.1236966
|View full text |Cite
|
Sign up to set email alerts
|

Dry Eye Disease in Patients with Newly Diagnosed Depressive Disorder

Abstract: Our study shows a definite association between depression and DED. We feel that it is important that psychiatrists take this into account especially while prescribing antidepressants which may aggravate dry eye signs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
4
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 18 publications
2
44
4
3
Order By: Relevance
“…Previous studies, mostly involving epidemiological questionnaires, have also reported a relationship between depression and dry eye disease [23][24][25][26]. In a comparison of depressive and control groups, one case-control study revealed significantly lower Schirmer scores and shorter TBUT, as well as a consistently higher Oxford scores in individuals with depression [27]. Similarly, we demonstrated an association between depression/anti-depressant use and dry eye severity by undertaking objective measurements, although the mechanisms involved in this association remain unknown.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies, mostly involving epidemiological questionnaires, have also reported a relationship between depression and dry eye disease [23][24][25][26]. In a comparison of depressive and control groups, one case-control study revealed significantly lower Schirmer scores and shorter TBUT, as well as a consistently higher Oxford scores in individuals with depression [27]. Similarly, we demonstrated an association between depression/anti-depressant use and dry eye severity by undertaking objective measurements, although the mechanisms involved in this association remain unknown.…”
Section: Discussionmentioning
confidence: 92%
“…28 Tiskaoglu et al also found results similar to the present study, with Schirmer's test values being significantly lower in patients diagnosed with depression compared to patients without depression. 29 However, Labbe et al, who also assessed a correlation of depression score with Schirmer test and TBUT, failed to derive a significant result. 30 Li et al also failed to find a significant correlation between depression scores and Schirmer's and TBUT scores.…”
Section: Discussionmentioning
confidence: 99%
“…But these studies only examined clinical signs of dry eye and did not reveal how this is related to eye symptoms experienced by patients. Another study found that newly-depressed and yet not medicated patients (some of them with comorbid anxiety) had more severe clinical signs of DED compared with the control group measured by objective tests, but there were no differences according to self-reported dry eye symptoms (50). However, these results are not yet fully established because other results showed the opposite (11).…”
Section: Preporuke Za Zbrinjavanje Pacijenatamentioning
confidence: 97%